2012
DOI: 10.1021/jm3010114
|View full text |Cite
|
Sign up to set email alerts
|

Organosilicon Molecules with Medicinal Applications

Abstract: The incorporation of silicon and synthesis of organosilicon small molecules provide unique opportunities for medicinal applications. The biological investigation of organosilicon small molecules is particularly interesting because of differences in their chemical properties that can contribute to enhanced potency and improved pharmacological attributes. Applications such as inhibitor design, imaging, drug release technology, and mapping inhibitor binding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
368
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 846 publications
(383 citation statements)
references
References 113 publications
3
368
0
12
Order By: Relevance
“…[1][2][3][4] In recent years, various silicon-containing bioactive compounds have been reported, such as BNP1350 (1), sila-haloperidol (2) and TAC101 (3) (Fig. 1), [5][6][7] and clinical studies have supported the idea that sila-substitution can improve the selectivity, potency and pharmacokinetics of drug candidates.…”
mentioning
confidence: 97%
“…[1][2][3][4] In recent years, various silicon-containing bioactive compounds have been reported, such as BNP1350 (1), sila-haloperidol (2) and TAC101 (3) (Fig. 1), [5][6][7] and clinical studies have supported the idea that sila-substitution can improve the selectivity, potency and pharmacokinetics of drug candidates.…”
mentioning
confidence: 97%
“…2 Growing interest in the utility of (hetero)arylsilanes in synthesis, 3 medicinal chemistry 4 and materials science 5 has fuelled the development of powerful C-H silylation methods, 6,7 as exemplified by recent work on indole substrates (Figure 1). Rh-7b , Ir-8 and even t BuOKcatalysed 9 reactions have been shown to deliver C2-silylated indoles selectively, whilst C3-H silylation has been achieved using more specialised Ru complexes.…”
Section: Ru-catalysed C-h Silylation Of Unprotected Gramines Tryptammentioning
confidence: 99%
“…Also no well-known intrinsic "element-specific" toxicity is related to organosilicon molecules. 22 Recently, it has been reported that the C/Si exchange has lead to the identification of potent p38 allosteric inhibitors. 23 The present study was performed to understand the binding mechanism of allosteric inhibitors and p38 in DFG-out conformation, by combining molecular docking, dynamics simulation, MM-GBSA free energy calculation and per residue energy decomposition techniques.…”
Section: 18mentioning
confidence: 99%